Integrative Approach to Learning Content and Teaching - Filduza Prušević Sadović (Društvene i Humanističke Studije, 2017)
. Integrative instruction and integrative approach to learning content created as an attempt to overcome the lack of traditional teaching that results from the division of educational content on the blocks, or subjects. A good part of the learning contents are repeated through different courses. However, they do not link which leads to confusion among students, what this system leads to some content the students never learn properly. This approach discourages students learning in the process of gaining new knowledge and application of knowledge gained in practice. An integrative approach to teaching exceeds the disadvantages described arguing for the removal of boundaries between subjects and focusing on a broad topic of study. By providing a holistic rather than fragmented view of learning, students become greatly clearer and more accessible about teaching topics, the students get a realistic picture of the world and the problems to be addressed. Application of integrated teaching is a strategy of teaching and learning based on the assumption that learning is a set of links. Teaching and learning integrated learning content can be useful for students and for teachers as cultivating a particular theme of her approach using various forms and methods, teaching materials and resources. In this way, students can have a natural way of acquiring knowledge through the development of different skills and abilities.Also, covering a wide field of educational content, the teacher is able to use the students' interest and motivation as well as drivers of meaningful learning, builds teaching skills enabled him greater flexibility in teaching.The paper discusses the advantages of integrated teaching compared to traditional, effects that it achieved the quality of knowledge and activity of students, as well as the effects that this has on the teaching model for teachers and creating ways of teaching content. The paper also discusses the possibilities of application of integrative model of teaching in elementary grades.